Compound corrosion inhibitor for gathering pipeline of oil and gas field and preparation method of compound corrosion inhibitor
By combining the components such as fluorine-containing imidazoline oleate, quinoline quaternary ammonium salt, carbon quantum dots in the corrosion inhibitor, combined with surfactant and antioxidant, the corrosion problem of oil and gas fields under CO2 oil flooding technology is solved, and the corrosion problem of oil and gas fields has been achieved in The efficient corrosion-proof effect under neutral or acidic media reduces the concentration and cost of use and ensures environmental protection.
Patent Information
- Application Number
- CN202411387306.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-10
AI Technical Summary
CO2 oil flooding technology leads to an increase in CO2 concentration in oil and gas fields, resulting in serious corrosion problems. The existing corrosion inhibitors are not effective in neutral or acidic media environments, and some are toxic and costly.
Provides a composite corrosion inhibitor including imidazoline fluorine oleate, quinoline quaternary ammonium salt, carbon quantum dots, surfactants, complexing agents, antioxidants and nanomesoporous silica, to reduce corrosion by synergistically Rate, suitable for neutral or acidic media environments, and is non-toxic and contaminated.
It significantly slows down the corrosion rate of oil and gas field collection and transportation pipelines under neutral or acidic media, has low usage concentration (60-120mg/L), low cost, and is non-toxic and pollution-free, improving the adaptability and stability of corrosion inhibitors.
Smart Images

Figure BDA0005071224600000091 
Figure BDA0005071224600000092 
Figure BDA0005071224600000101
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of oil and gas field gathering and transportation pipeline steel corrosion and protection, and in particular to a composite corrosion inhibitor for oil and gas field gathering and transportation pipeline and a preparation method thereof. Background Art
[0002] In view of the fact that the large-scale application of CO2 flooding technology has led to a significant increase in the CO2 concentration in oil and gas fields, the corrosion problem caused by this has become increasingly serious. CO2 corrosion is mainly a fluid mechanics and chemical corrosion. The fluid mechanics is mainly manifested in the acceleration of corrosion product film, which leads to accelerated corrosion. Specifically, CO2 dissolves in water to generate H2CO3, making the solution acidic, aggravating the hydrogen depolarization reaction of carbon steel materials, significantly increasing the corrosion rate of carbon steel, and posing a serious threat to the safe and stable operation of oil and gas pipeline steel.
[0003] In order to control the corrosion of oil and gas field gathering and transportation pipelines, commonly used corrosion inhibitors are divided into two categories: inorganic and organic. Inorganic corrosion inhibitors include chromates, molybdates, phosphates and nitrates, while organic corrosion inhibitors are mainly imidazolines, amines, pyridines and quinolines. However, it is sometimes difficult to achieve the desired effect with a single corrosion inhibitor in actual production and use. Compounding corrosion inhibitors with other surfactants can enhance the corrosion inhibition effect of corrosion inhibitors, reduce the amount of main materials, and reduce production costs. At present, the commonly used corrosion inhibitors for CO2 corrosion environments are mainly imidazoline derivatives, compound thiourea, L-cysteine, pyridine quaternary ammonium salts, Gemini surfactants, etc. Among them, compound thiourea and L-cysteine are expensive and have different optimal concentrations in different corrosive media. Too high or too low concentrations will promote corrosion. In addition, although these corrosion inhibitors can effectively inhibit corrosion, they often require a higher concentration of 300-500 mg / L, and some are toxic. Summary of the invention
[0004] The present invention aims to provide a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines and a preparation method thereof in view of the difficulties existing in the current technology. The present invention is green and environmentally friendly and the composite corrosion inhibitor is particularly suitable for neutral or acidic corrosive medium environments, and can effectively slow down the corrosion rate of gathering and transportation pipelines in neutral or acidic media.
[0005] The present invention provides a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines and a preparation method thereof, which can be achieved by the following technical solutions:
[0006] A composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, which comprises, by mass percentage, 59-64% of a main material, 30-33% of an auxiliary material and 3-11% of a filler. The main material comprises fluorinated oleic acid imidazoline, quinoline quaternary ammonium salt and carbon quantum dots; the auxiliary material comprises a surfactant, a complexing agent and an antioxidant; and the filler is nano-mesoporous silica.
[0007] Based on the above technical solution, the present invention can also be improved as follows:
[0008] One of the technical solutions of the present invention is to provide a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, wherein the complexing agent is two or more of polyhydroxy acrylic acid, sodium hexametaphosphate, and tartaric acid. Complexing agents such as polyhydroxy acrylic acid, sodium hexametaphosphate, and tartaric acid contain multiple negatively charged phosphate groups or hydroxyl groups, which have a strong chelating effect on metals, and after being compounded with another complexing agent, a synergistic effect is generated between them. The complexing agent can adapt to different corrosive environments and improve the adaptability and extensiveness of the corrosion inhibitor.
[0009] One of the technical solutions of the present invention is to provide a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, wherein the surfactant is two or more of sodium dodecyl sulfonate, tetradecyl trimethyl ammonium bromide cation, and nonylphenol polyoxyethylene ether. The role of the surfactant is that it can significantly reduce the interfacial tension between the solvent and the metal surface, improve the adsorption efficiency of the corrosion inhibitor molecules on the metal surface; by changing the active sites on the metal surface, the adsorption of the corrosion inhibitor molecules on the metal surface is enhanced, which helps to form a stable and uniform corrosion inhibition film, and further improves the corrosion inhibition performance. The composite use of two surfactants in the corrosion inhibitor can achieve multi-faceted optimization. First, this composite corrosion inhibitor produces a synergistic corrosion inhibition effect, and through the joint action of different corrosion inhibition mechanisms, it controls the corrosion process more comprehensively and improves the corrosion inhibition efficiency. Secondly, the surfactant helps to improve the stability of the corrosion inhibitor and ensure its long-term effectiveness. Finally, the reasonable adjustment of the ratio of the two surfactants helps to adjust the cost, so that the corrosion inhibitor has better economy while maintaining high corrosion inhibition efficiency.
[0010] One of the technical solutions of the present invention is to provide a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, wherein the mass content ratios of the fluorinated oleic acid imidazoline, quinoline quaternary ammonium salt and carbon quantum dots as main ingredients are 6:4:3 respectively.
[0011] One of the technical solutions of the present invention is to provide a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, wherein the antioxidant is two or more of phytic acid, sodium benzoate, and paraben. For metal gathering and transportation pipelines, the role of antioxidants is to improve the corrosion resistance of metals and protect metal materials from oxidation and corrosion damage mainly by inhibiting the generation of free radicals, stabilizing the metal surface, consuming corrosive media, etc. Antioxidants can react with oxides or other corrosion products formed on the metal surface to form a stable protective layer to prevent further oxidation reactions. Using two antioxidants at the same time can enhance the overall antioxidant capacity because they can play a complementary role against different types of free radicals and oxidative stress. This combination not only improves the antioxidant effect, but also reduces the side effects that may occur when a single antioxidant is used in high doses.
[0012] One of the technical solutions of the present invention is to provide a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, wherein the filler is nano-mesoporous silica.
[0013] One of the technical solutions of the present invention is that the aqueous solution of ethanol is the solvent.
[0014] One of the technical solutions of the present invention is that the volume ratio of the total material to the ethanol aqueous solution is 1:25.
[0015] One of the technical solutions of the present invention is to provide a method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, which specifically comprises the following steps:
[0016] S1: First add the complexing agent raw material into the ethanol aqueous solution at room temperature, with the volume ratio of alcohol to water being 72:28. After it is completely dissolved, add the surfactant and continue stirring for half an hour.
[0017] S2: Heat the above solution to 50-70°C, add quinoline quaternary ammonium salt, carbon quantum dots and fluorinated oleic acid imidazoline in sequence, control the stirring speed at 100-200 r / min, stir for 1.5-2.5 hours, and then add antioxidant.
[0018] S3: Cool the solution to room temperature, add filler, and react at 100-120° C. for 5-24 hours. Finally, centrifuge, wash, and vacuum dry for 48 hours to obtain a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines.
[0019] In S3, the average particle size of the mesoporous silica can be adjusted according to specific needs, generally in the range of 20 to 50 nm.
[0020] The composite corrosion inhibitor for oil and gas field gathering and transportation pipelines of the present invention is used in the aspect of corrosion inhibition of oil and gas field gathering and transportation pipelines. The pH value of the application environment is 3-8 and the dosage is 60-120 mg / L.
[0021] The beneficial effects of the present invention are mainly reflected in that: fluorinated oleic acid imidazoline is a special corrosion inhibitor, which combines the corrosion inhibition performance of imidazoline derivatives and the characteristics of fluorinated oleic acid, improved polarity, better thermal stability and unique molecular structure, all of which can enhance its corrosion inhibition effect in neutral or acidic corrosive medium environments. Its main function is that the reactive regions of oleic acid imidazoline molecules are distributed on the imidazole ring and its polar functional groups of the molecule. The three N atoms on the imidazole ring and the polar functional group are electrophilic reaction centers, and the electrons form coordination bonds with the metal surface so that oleic acid imidazoline is chemically adsorbed on the metal surface; at the same time, the C and N atoms in the double bond structure on the imidazole ring are nucleophilic reaction centers, which can accept the electrons provided by the metal surface to form feedback bonds. The N atoms on the quinoline ring of the quinoline quaternary ammonium salt can also accept the electrons provided by the metal surface to form feedback bonds.
[0022] The present invention provides a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, wherein carbon quantum dots have the advantages of small size and high specific surface area. Carbon quantum dots not only have good water solubility, but also have good adsorption and film-forming properties on metal surfaces, and can effectively improve the corrosion resistance of the corrosion inhibitor. They interact with the metal surface through abundant active sites, effectively slowing down the corrosion rate of the metal, and at the same time, due to their electrochemical stability, they can maintain a long-term corrosion inhibition effect in a neutral or acidic corrosive medium environment.
[0023] The present invention provides a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines. The role of mesoporous silica is that mesoporous silica, as an effective carrier of the corrosion inhibitor, increases the contact area between the corrosion inhibitor molecules and the metal surface, thereby improving the corrosion inhibition efficiency. At the same time, the mesoporous silica can react with oxides or other corrosion products on the metal surface to form a dense corrosion inhibition film, effectively preventing further contact with the corrosive medium, thereby comprehensively improving the performance and application effect of the corrosion inhibitor.
[0024] The present invention does not contain expensive components such as compound thiourea and L-cysteine, and has a lower price; the present invention can be used in neutral or acidic media, does not need to consider the influence of the pH of the medium too much, and will not promote corrosion; the existing corrosion inhibitors are generally used at a concentration of 300-500 mg / L, while the present invention uses a concentration of 60-120 mg / L, with less usage and is non-toxic. The present invention provides a preparation method for a compound corrosion inhibitor for oil and gas field gathering and transportation pipelines, which has simple preparation operation, low cost, small addition amount, is non-toxic and pollution-free, and meets environmental protection requirements. DETAILED DESCRIPTION
[0025] In order to facilitate understanding of the present application, the present application will be described more comprehensively below. The present application can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the disclosure of the present application more thorough and comprehensive.
[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application.
[0027] In order to make the purpose, technical solutions and advantages of the present invention more clear, the invention will be further described in detail through embodiments below. The protection scope of the present invention is not limited to the following embodiments.
[0028] Example 1
[0029] A composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is composed of the following mass percentage components: 59% main material, 33% auxiliary material and 8% filler. The main material includes fluorinated oleic acid imidazoline, quinoline quaternary ammonium salt and carbon quantum dots, and the mass ratio is 6:4:3; auxiliary materials: surfactant is 5% sodium dodecyl sulfonate and 4% tetradecyl trimethyl ammonium bromide cation; complexing agent is 7% polyhydroxyacrylic acid, 6% sodium hexametaphosphate, 6% tartaric acid; antioxidant includes 3% phytic acid and 2% sodium benzoate; filler is mesoporous silica with a particle size of 20nm.
[0030] A method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, the preparation process of the corrosion inhibitor specifically comprises the following steps:
[0031] S1: First add the complexing agent raw material into an ethanol aqueous solution (the volume ratio of alcohol to water is 72:28) at room temperature, add the surfactant after it is completely dissolved, and continue stirring for half an hour.
[0032] S2: The above solution is heated to 50° C., and quinoline quaternary ammonium salt, carbon quantum dots and fluorinated oleic acid imidazoline are added in sequence. The stirring speed is controlled at 100 r / min. After stirring for 2 hours, an antioxidant is added.
[0033] S3: The solution is cooled to room temperature, a filler is added, and the mixture is reacted at 100° C. for 5 hours. Finally, a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is obtained by centrifugation, washing, and vacuum drying for 48 hours.
[0034] Example 2
[0035] A composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is composed of the following mass percentage components: 64% main material, 30% auxiliary material and 6% filler. The main material includes fluorinated oleic acid imidazoline, quinoline quaternary ammonium salt and carbon quantum dots, and the mass ratio is 6:4:3; auxiliary materials: surfactant is 5% tetradecyl trimethyl ammonium bromide cation, 8% nonylphenol polyoxyethylene ether; complexing agent is 5% polyhydroxy acrylic acid, 7% sodium hexametaphosphate; antioxidant includes 2% phytic acid, 3% paraben; filler is mesoporous silica with a particle size of 30nm.
[0036] A method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, the preparation process of the corrosion inhibitor specifically comprises the following steps:
[0037] S1: First add the complexing agent raw material into an ethanol aqueous solution (the volume ratio of alcohol to water is 72:28) at room temperature, add the surfactant after it is completely dissolved, and continue stirring for half an hour.
[0038] S2: The above solution is heated to 70° C., and quinoline quaternary ammonium salt, carbon quantum dots and fluorinated oleic acid imidazoline are added in sequence. The stirring speed is controlled at 200 r / min. After stirring for 2 hours, an antioxidant is added.
[0039] S3: The solution is cooled to room temperature, a filler is added, and the mixture is reacted at 120° C. for 5 hours. Finally, a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is obtained by centrifugation, washing, and vacuum drying for 48 hours.
[0040] Example 3
[0041] A composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is composed of the following mass percentage components: 64% main material, 33% auxiliary material and 3% filler. The main material includes fluorinated oleic acid imidazoline, quinoline quaternary ammonium salt and carbon quantum dots, and the mass ratio is 6:4:3; auxiliary materials: surfactant is 10% sodium dodecyl sulfonate, 2% tetradecyl trimethyl ammonium bromide cation, 3% nonylphenol polyoxyethylene ether; complexing agent is 8% polyhydroxy acrylic acid, 7% tartaric acid; antioxidant includes 1% phytic acid, 2% paraben; filler is mesoporous silica with a particle size of 40nm.
[0042] A method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, the preparation process of the corrosion inhibitor specifically comprises the following steps:
[0043] S1: First add the complexing agent raw material into an ethanol aqueous solution (the volume ratio of alcohol to water is 72:28) at room temperature, add the surfactant after it is completely dissolved, and continue stirring for half an hour.
[0044] S2: The above solution is heated to 65°C, and quinoline quaternary ammonium salt, carbon quantum dots and fluorinated oleic acid imidazoline are added in sequence. The stirring speed is controlled at 180 r / min. After stirring for 2 hours, an antioxidant is added.
[0045] S3: The solution is cooled to room temperature, a filler is added, and the mixture is reacted at 110° C. for 5 hours. Finally, a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is obtained by centrifugation, washing, and vacuum drying for 48 hours.
[0046] Example 4
[0047] A composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is composed of the following mass percentage components: 59% main material, 30% auxiliary material and 11% filler. The main material includes fluorinated oleic acid imidazoline, quinoline quaternary ammonium salt and carbon quantum dots, and the mass ratio is 6:4:3; auxiliary materials: surfactant is 9% sodium dodecyl sulfonate, 3% tetradecyl trimethyl ammonium bromide cation, 3% nonylphenol polyoxyethylene ether; complexing agent is 3% polyhydroxy acrylic acid, 7% tartaric acid, 1% sodium hexametaphosphate; antioxidant includes 2% sodium benzoate and 2% paraben; filler is mesoporous silica with a particle size of 50nm.
[0048] A method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, the preparation process of the corrosion inhibitor specifically comprises the following steps:
[0049] S1: First add the complexing agent raw material into an ethanol aqueous solution (the volume ratio of alcohol to water is 72:28) at room temperature, add the surfactant after it is completely dissolved, and continue stirring for half an hour.
[0050] S2: The above solution is heated to 60° C., and quinoline quaternary ammonium salt, carbon quantum dots and fluorinated oleic acid imidazoline are added in sequence. The stirring speed is controlled at 160 r / min. After stirring for 2 hours, an antioxidant is added.
[0051] S3: The solution is cooled to room temperature, a filler is added, and the mixture is reacted at 105° C. for 5 hours. Finally, a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is obtained by centrifugation, washing, and vacuum drying for 48 hours.
[0052] Example 5
[0053] A composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is composed of the following mass percentage components: 62% main material, 31% auxiliary material and 7% filler. The main material includes fluorinated oleic acid imidazoline, quinoline quaternary ammonium salt and carbon quantum dots, and the mass ratio is 6:4:3; auxiliary materials: surfactant is 9% sodium dodecyl sulfonate, 5% nonylphenol polyoxyethylene ether; complexing agent is 3% polyhydroxyacrylic acid, 4% tartaric acid, 2% sodium hexametaphosphate; antioxidant includes 4% phytic acid, 2% sodium benzoate, 2% paraben; filler is mesoporous silica with a particle size of 30nm.
[0054] A method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, the preparation process of the corrosion inhibitor specifically comprises the following steps:
[0055] S1: First add the complexing agent raw material into an ethanol aqueous solution (the volume ratio of alcohol to water is 72:28) at room temperature, add the surfactant after it is completely dissolved, and continue stirring for half an hour.
[0056] S2: Heat the above solution to 70°C, add quinoline quaternary ammonium salt, carbon quantum dots and fluorinated oleic acid imidazoline in sequence, control the stirring speed at 180r / min, stir for 2 hours, and then add antioxidant.
[0057] S3: The solution is cooled to room temperature, a filler is added, and the mixture is reacted at 105° C. for 5 hours. Finally, a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is obtained by centrifugation, washing, and vacuum drying for 48 hours.
[0058] The test method for corrosion inhibition efficiency is:
[0059] The in-situ electrochemical test of the composite corrosion inhibitor involved in the present invention has the following specific steps:
[0060] In-situ electrochemical testing was performed using a three-electrode system, with a saturated calomel electrode as the reference electrode, the sample being tested as the working electrode, and a platinum sheet as the platinum electrode.
[0061] The measured potential values are all relative to the reference electrode SCE, and the in situ electrochemical tests were carried out at 25°C.
[0062] The experimental material is N80 steel sheet, which is processed into a square shape and welded with a copper wire at one end for in-situ electrochemical testing. 2 The surface area of the sample was used as the working surface, and the non-working surface was sealed with epoxy resin, leaving the working surface unsealed to prevent crevice corrosion. The working surface was polished to a mirror finish with a series of sandpapers (120#, 400#, 800#, 1000#, 2000#) and cleaned with alcohol or acetone. The treated samples were stored in a desiccator for experimental use.
[0063] The pretreated N80 carbon steel was subjected to in-situ electrochemical experiments in a CO2-saturated NaCl solution at 25°C. After stabilization at open circuit potential (OCP) for 2 hours, the 5 -10 -2 Electrochemical impedance spectroscopy (EIS) measurements were performed at a frequency of 10 Hz and an AC interference of 10 mV. Potentiodynamic polarization tests were performed with a scan rate of 1.0 mV / S in the range of -1.0 V to 0.0 V versus a saturated calomel electrode (vs. SCE).
[0064] Corrosion inhibition efficiency of N80 carbon steel in CO2 saturated NaCl solution before and after adding composite corrosion inhibitor It is calculated by the following formula:
[0065]
[0066] Where R total(inh) is the total resistance of N80 carbon steel after adding the compound corrosion inhibitor in each implementation case, R total(空白) is the total resistance of N80 carbon steel without adding compound corrosion inhibitor, which is 128.03Ωcm 2 The added concentration of the compound corrosion inhibitor is 60-120 mg / L, and the corrosion inhibition efficiency of the compound corrosion inhibitor prepared in each example is tested within this concentration range.
[0067] Table 1 shows the fitting parameters of the electrochemical impedance curves of N80 carbon steel measured in CO2 saturated NaCl solution in Examples 1 to 5.
[0068] Table 1 is a comparison of impedance fitting data of the composite corrosion inhibitors prepared in Examples 1 to 5
[0069]
[0070] According to the data in Table 1, the composite corrosion inhibitor prepared in Example 3 exhibits a corrosion inhibition efficiency of up to 96.6%, which is better than the corrosion inhibitors in the other four examples. The results show that the corrosion inhibitor in Example 3 performs best among Examples 1 to 5.
[0071] Comparative Example 1
[0072] A composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is composed of the following mass percentage components: 64% main material, 30% auxiliary material and 6% filler. The main material includes fluorinated oleic acid imidazoline and carbon quantum dots, and the ratio is 7:3; auxiliary materials: surfactant is 6% tetradecyl trimethyl ammonium bromide cation, 8% nonylphenol polyoxyethylene ether; complexing agent is 4% polyhydroxy acrylic acid, 6% sodium hexametaphosphate; antioxidant includes 3% phytic acid, 3% paraben; filler is mesoporous silica with a particle size of 40nm.
[0073] A method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, the preparation process of the corrosion inhibitor specifically comprises the following steps:
[0074] S1: First add the complexing agent raw material into an ethanol aqueous solution (the volume ratio of alcohol to water is 72:28) at room temperature, add the surfactant after it is completely dissolved, and continue stirring for half an hour.
[0075] S2: The above solution was heated to 65°C, and carbon quantum dots and fluorinated oleic acid imidazoline were added successively. The stirring speed was controlled at 160 r / min. After stirring for 2 hours, an antioxidant was added.
[0076] S3: The solution is cooled to room temperature, a filler is added, and the mixture is reacted at 110° C. for 5 hours. Finally, a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is obtained by centrifugation, washing, and vacuum drying for 48 hours.
[0077] Table 2 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared by comparative example 1 and the composite corrosion inhibitor of embodiment 3. It can be seen from Table 2 that when the main material does not add quinoline quaternary ammonium salt, the corrosion inhibition efficiency of the corrosion inhibitor is significantly lower than that of embodiment 3, and its corrosion inhibition efficiency only reaches 82.7%. The reason is that quinoline quaternary ammonium salt, as an efficient corrosion inhibitor, has a multifaceted protection mechanism. The nitrogen atoms it contains can be combined with the active hydrogen ions on the metal surface through coordination bonds, effectively reducing the charge density of the metal, and then reducing the occurrence of electrochemical corrosion. In the corrosion process, quinoline quaternary ammonium salt reacts chemically with the oxide on the metal surface to generate a stable protective film, reduce the dissolution of the metal in the corrosive environment, thereby improving the corrosion resistance of the metal material.
[0078] Table 2 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared in Comparative Example 1 and the best composite corrosion inhibitor in Example 3
[0079]
[0080] Comparative Example 2
[0081] A composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is composed of the following mass percentage components: 64% main material, 30% auxiliary material and 6% filler. The main material includes fluorinated oleic acid imidazoline and quinoline quaternary ammonium salt, and the ratio is 7:3; auxiliary materials: surfactant is 5% tetradecyl trimethyl ammonium bromide cation, 8% nonylphenol polyoxyethylene ether; complexing agent is 5% polyhydroxy acrylic acid, 7% sodium hexametaphosphate; antioxidant includes 2% phytic acid, 3% paraben; filler is mesoporous silica with a particle size of 40nm.
[0082] A method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, the preparation process of the corrosion inhibitor specifically comprises the following steps:
[0083] S1: First add the complexing agent raw material into an ethanol aqueous solution (the volume ratio of alcohol to water is 72:28) at room temperature, add the surfactant after it is completely dissolved, and continue stirring for half an hour.
[0084] S2: The above solution is heated to 65° C., and quinoline quaternary ammonium salt and fluorinated oleic acid imidazoline are added successively. The stirring speed is controlled at 100 r / min. After stirring for 2 hours, an antioxidant is added.
[0085] S3: The solution is cooled to room temperature, a filler is added, and the mixture is reacted at 100° C. for 5 hours. Finally, a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is obtained by centrifugation, washing, and vacuum drying for 48 hours.
[0086] Table 3 is a comparison of impedance fitting data of the compound corrosion inhibitor prepared by comparative example 2 and the compound corrosion inhibitor of embodiment 3. It can be seen from Table 3 that when carbon quantum dots are not added to the main material, the corrosion inhibition efficiency of the corrosion inhibitor is significantly lower than that of embodiment 3, and its corrosion inhibition efficiency is only 85.1%. The reason is that carbon quantum dots have the advantages of small size and high specific surface area, and show remarkable performance in the field of corrosion inhibitors. They interact with the metal surface by providing abundant active sites, effectively slowing down the corrosion rate of the metal. At the same time, due to their electrochemical stability, they can maintain a long-term corrosion inhibition effect in a neutral or acidic corrosive medium environment.
[0087] Table 3 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared in Comparative Example 2 and the best composite corrosion inhibitor in Example 3
[0088]
[0089] Comparative Example 3
[0090] A composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is composed of the following mass percentage components: 50% main material, 47% auxiliary material and 3% filler. The main material includes fluorinated oleic acid imidazoline, quinoline quaternary ammonium salt and carbon quantum dots, and the mass ratio is 6:4:3; auxiliary materials: surfactant is 17% sodium dodecyl sulfonate, 13% nonylphenol polyoxyethylene ether; complexing agent is 4% polyhydroxyacrylic acid, 3% tartaric acid, 2% sodium hexametaphosphate; antioxidant includes 4% phytic acid, 2% sodium benzoate, 2% paraben; filler is mesoporous silica with a particle size of 40nm.
[0091] A method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, the preparation process of the corrosion inhibitor specifically comprises the following steps:
[0092] S1: First add the complexing agent raw material into an ethanol aqueous solution (the volume ratio of alcohol to water is 72:28) at room temperature, add the surfactant after it is completely dissolved, and continue stirring for half an hour.
[0093] S2: Heat the above solution to 70°C, add quinoline quaternary ammonium salt, carbon quantum dots and fluorinated oleic acid imidazoline in sequence, control the stirring speed at 180r / min, stir for 2 hours, and then add antioxidant.
[0094] S3: The solution is cooled to room temperature, a filler is added, and the mixture is reacted at 100° C. for 5 hours. Finally, a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines is obtained by centrifugation, washing, and vacuum drying for 48 hours.
[0095] Table 4 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared by comparative example 3 and the composite corrosion inhibitor of embodiment 3. It can be seen from Table 4 that when the main ingredient ratio decreases and the auxiliary ingredient ratio increases, the corrosion inhibition efficiency of the corrosion inhibitor is significantly lower than that of embodiment 3, and its corrosion inhibition efficiency is only 81.9%. The results show that fluorine-containing oleic acid imidazoline and quinoline quaternary ammonium salt can form a stable adsorption layer on the metal surface, effectively isolating the corrosive medium, and the addition of carbon quantum dots further regulates the electronic state of the metal surface and reduces the corrosion rate through its unique electronic structure and quantum confinement effect. The combination of these two effects, plus the synergistic adsorption effect of the functional groups between fluorine-containing oleic acid imidazoline and quinoline quaternary ammonium salt, makes the protective film more uniform and dense.
[0096] Table 4 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared in Comparative Example 3 and the best composite corrosion inhibitor in Example 3
[0097]
[0098] Comparative Example 4
[0099] This comparative example is substantially the same as the best embodiment, except that the fluorine-containing oleic acid imidazoline is replaced by fluorine-free oleic acid imidazoline.
[0100] Table 5 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared by Comparative Example 4 and the composite corrosion inhibitor of Example 3. It can be seen from Table 5 that the corrosion inhibition efficiency of the corrosion inhibitor is significantly lower than that of Example 3 when the fluorine-containing oleic acid imidazoline is replaced by fluorine-free oleic acid imidazoline, and its corrosion inhibition efficiency is only 83.2%. Due to the high polarity brought by fluorine atoms, the fluorine-containing oleic acid imidazoline has a better corrosion inhibition effect when treating polar H2CO3 corrosive media. At the same time, its thermal stability is enhanced and the corrosion inhibition effect can be maintained at high temperatures. The higher polarity and molecular structure improvement make it have better dispersibility, can effectively mix with the corrosive medium, reduce direct damage to the metal, and form a denser protective film, which can effectively prevent further erosion of the corrosive medium.
[0101] Table 5 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared by Comparative Example 4 and the best composite corrosion inhibitor of Example 3
[0102]
[0103] Comparative Example 5
[0104] This comparative example is substantially the same as the preferred embodiment, except that only tartaric acid is used as a complexing agent, and its content is 15%.
[0105] Table 6 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared by Comparative Example 5 and the composite corrosion inhibitor of Example 3. It can be seen from Table 6 that when only tartaric acid is used as a complexing agent, the corrosion inhibition efficiency of the corrosion inhibitor is significantly lower than that of Example 3, and its corrosion inhibition efficiency is only 88.1%. The results show that in the preparation of the corrosion inhibitor, the three complexing agents of polyhydroxyacrylic acid, tartaric acid and sodium hexametaphosphate show a synergistic effect, thereby significantly improving the corrosion inhibition effect. Tartaric acid, as an organic acid, can reduce the pH value of the solution and create an environment that is not conducive to corrosion reactions, while polyhydroxyacrylic acid has a buffering capacity, which helps to stabilize the pH value and ensure that the metal is in a corrosion-inhibiting pH environment. In addition, the three complexing agents each complement each other in their complexing ability for different metal ions, and together form a comprehensive complexing system to further improve the corrosion inhibition effect.
[0106] Table 6 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared in Comparative Example 5 and the best composite corrosion inhibitor in Example 3
[0107]
[0108] Comparative Example 6
[0109] This comparative example is substantially the same as the best embodiment, except that only one antioxidant, phytic acid, is used, and its content is 3%.
[0110] Table 7 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared by Comparative Example 6 and the composite corrosion inhibitor of Example 3. It can be seen from Table 7 that when only one antioxidant is used, the corrosion inhibition efficiency of the corrosion inhibitor is significantly lower than that of Example 3, and its corrosion inhibition efficiency is only 88.7%. The results show that the three antioxidants, phytic acid, sodium benzoate and paraben, have a synergistic effect in corrosion inhibition. The hydrogen ions provided by sodium benzoate can react with the phosphate ions in the metal complex formed by phytic acid to neutralize, which helps to stabilize the metal surface and reduce corrosion; the combined action of phytic acid and sodium benzoate can form a complex system on the metal surface, which has both an acidic environment and a protective film; parabens indirectly reduce corrosion by inhibiting microbial growth, while the other two substances reduce corrosion by directly reacting with the metal.
[0111] Table 7 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared by Comparative Example 6 and the best composite corrosion inhibitor of Example 3
[0112]
[0113] Comparative Example 7
[0114] This comparative example is substantially the same as the best embodiment, except that no mesoporous silica filler is added.
[0115] Table 8 is a comparison of the impedance fitting data of the compound corrosion inhibitor prepared by Comparative Example 7 and the compound corrosion inhibitor of Example 3. It can be seen from Table 8 that when no mesoporous silica filler is added, the corrosion inhibition efficiency of the corrosion inhibitor is significantly lower than that of Example 3, and its corrosion inhibition efficiency is only 86.3%.
[0116] Mesoporous silica, due to its high specific surface area and adjustable surface properties, can be used as an ideal carrier for corrosion inhibitor molecules, effectively improving the stability and efficiency of corrosion inhibitors. Its pore structure helps corrosion inhibitor molecules reach the metal surface more efficiently and form a protective film, thereby improving corrosion inhibition efficiency. At the same time, mesoporous silica can improve the dispersibility of corrosion inhibitors and prevent them from precipitating during storage or use. By adjusting the pore structure of mesoporous silica, the controlled release of corrosion inhibitors can be achieved and their service life can be extended.
[0117] Table 8 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared by Comparative Example 7 and the best composite corrosion inhibitor of Example 3
[0118]
[0119] Comparative Example 8
[0120] This comparative example is basically the same as the best embodiment, except that the reaction temperature in the specific step S3 of the preparation method of the corrosion inhibitor is 80° C., and the rest remains unchanged.
[0121] Table 9 is a comparison of impedance fitting data of the compound corrosion inhibitor prepared by comparative example 8 and the compound corrosion inhibitor of Example 3. It can be seen from Table 9 that the corrosion inhibition efficiency of the corrosion inhibitor is significantly lower than that of Example 3, and its corrosion inhibition efficiency is only 87.5%. The results show that in the process of preparing the corrosion inhibitor, the change of reaction temperature has a significant effect on the performance of the corrosion inhibitor. Exceeding the temperature range of the reaction will reduce the adsorption rate and adsorption amount of the corrosion inhibitor molecules on the metal surface, reduce the adsorption equilibrium constant, and is not conducive to the synthesis of the corrosion inhibitor, but it may also be because of the side reaction or the destruction of the active group of the corrosion inhibitor, reducing the corrosion inhibition efficiency.
[0122] Table 9 is a comparison of impedance fitting data of the composite corrosion inhibitor prepared by Comparative Example 8 and the best composite corrosion inhibitor of Example 3
[0123]
[0124] The above examples and comparative examples show that the best composite corrosion inhibitor prepared from the main ingredients including fluorinated oleic acid imidazoline, quinoline quaternary ammonium salt and carbon quantum dots has a good inhibitory effect on neutral or acidic corrosive medium environments.
[0125] The above contents are only for explaining the technical idea of the present invention and cannot be used to limit the protection scope of the present invention. Any changes made on the basis of the technical solution in accordance with the technical idea proposed by the present invention shall fall within the protection scope of the claims of the present invention.
Claims
1. A composite corrosion inhibitor for oil and gas field gathering and transportation pipelines, characterized in that: In terms of mass percentage, the composite corrosion inhibitor comprises 59-64% of a main material, 30-33% of an auxiliary material and 3-11% of a filler; the main material comprises fluorinated oleic acid imidazoline, quinoline quaternary ammonium salt and carbon quantum dots; the auxiliary material comprises a surfactant, a chelating agent and an antioxidant; and the filler is nano-mesoporous silica.
2. The composite corrosion inhibitor for oil and gas field gathering and transportation pipeline according to claim 1, characterized in that: The mass content ratios of fluorinated oleic acid imidazoline, quinoline quaternary ammonium salt and carbon quantum dots in the main material are 6:4:3 respectively.
3. The composite corrosion inhibitor for oil and gas field gathering and transportation pipeline according to claim 1, characterized in that: The surfactant includes two or more of sodium dodecyl sulfate, tetradecyl trimethyl ammonium bromide cation, and nonylphenol polyoxyethylene ether.
4. The composite corrosion inhibitor for oil and gas field gathering and transportation pipeline according to claim 1, characterized in that: The complexing agent is two or more of polyhydroxyacrylic acid, sodium hexametaphosphate and tartaric acid.
5. The composite corrosion inhibitor for oil and gas field gathering and transportation pipeline according to claim 1, characterized in that: The antioxidant is two or more of phytic acid, sodium benzoate and paraben.
6. The method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipeline according to any one of claims 1 to 5, characterized in that: The preparation process of the corrosion inhibitor includes the following steps: S1: First add the complexing agent raw material to the ethanol aqueous solution at room temperature, add the surfactant after it is completely dissolved, and continue stirring for half an hour; S2: Heat the above solution to 50-70°C, add quinoline quaternary ammonium salt, carbon quantum dots and fluorinated oleic acid imidazoline in sequence, control the stirring speed at 100-200 r / min, stir for 1.5-2.5 hours, and then add antioxidant; S3: Cooling the above solution to room temperature, adding filler, and reacting at 100-120° C. for 5-24 hours; finally, obtaining a composite corrosion inhibitor for oil and gas field gathering and transportation pipelines through centrifugation, washing, and vacuum drying.
7. The method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipeline according to claim 6, characterized in that: In S3, the average particle size of the mesoporous silica is 20 to 50 nm.
8. The method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipeline according to claim 6, characterized in that: In the S1, the volume ratio of ethanol to water is 72:
28.
9. The method for preparing a composite corrosion inhibitor for oil and gas field gathering and transportation pipeline according to claim 6, characterized in that: The volume ratio of the total material to the ethanol aqueous solution is 1:
25.
10. The use of the composite corrosion inhibitor for oil and gas field gathering and transportation pipelines according to claim 6 in the aspect of corrosion inhibition of oil and gas field gathering and transportation pipelines, characterized in that: The pH value of its application environment is 3-8, and the dosage is 60-120 mg / L.
Citation Information
Cited By
Carbon dioxide-resistant corrosion inhibitor as well as preparation method and application thereof
CN121737716A